Patis from alamang a plant design - Chan, Edward L. (College of Engineering, 1975)
Capacity: 5,000 liters/day -- Land area: 2,000 sq. m. -- Fixed capital investment: P 2,601,260.80 -- Maximum annual production: 1,825,000 liters of patis, 435,094 kg. of condiment -- Total product cost at maximum production: P 5,100,000.00 -- Annual sales at maximum production: P 6,843,750.00 for patis, P 217,547.30 for condiment -- Percent recovery of raw patis: 89.5% -- Annual rate of return on investment: 64.1% -- Pay-out period: 1.04 years -- Break even point: 15.5% of maximum operating capacity